Fabrication of Synthetic Zeolite from Sinabung Mountain Volcanic Ash via Sol-Gel Method - Lumban Raja, Saur; Simatupang, Eka Bonita (Journal of Chemical Natural Resources, 2022)
Fabrication of synthetic zeolite from Sinabung Mountain volcanic ash by Sol-Gel method. The zeolite is obtained by extraction of alkalis sodium silicate and sodium aluminate. At first volcanic ash was characterized using XRF and XRD analyses. The XRF analysis shows that silica is 44.8%. In contrast, XRD analysis showed a sharp peak at a 2Ѳ corner area of 27.55o to express bonded with silica mineral salt. At the same time, the silica characterization is done by FT-IR analysis. The FT-IR analysis shows the presence of Si-O-Si groups at wave numbers 1064.71 cm-1, 786.96 cm-1 and Si-OH at wave 3749.62 cm-1 and 3448.72 cm-1, identifying the presence of silica. The synthetic zeolite characterization analysis obtained is FT-IR, XRD, SEM-EDX, and BET analysis. In the FT-IR analysis, the O-Si-O group was obtained at wave 987,85 cm-1 and O-Al-O at wave 447,89-585,30 cm-1, identifying X zeolite. Diffractogram XRD showed a sharp peak at 66.8°, 28.12°, and 45.84°, forming mixed crystalline X and zeolite A. SEM-EDX analysis shows that zeolite morphology is tight and homogeneous and has a high aluminium content of 24.79 and Si 16.12. While for nitrogen desorption, adsorption analysis on pore size, surface area and pore volume are 3,22 nm, 61,86 m2/g and 0,095 cc/g. The result of synthetic zeolite isotherm adsorption-desorption shows type V showing mesoporous size.